Identifying constraints and strategies for palm oil production in Indonesia: An interpretive structure model approach - Rosada, Ida; Nurliani; Amiruddin, Achmad; Novanda, Ridha Rizki (Asian Journal of Agriculture and Rural Development, 2025)
Palm oil plays an important role in the economy in Indonesia, particularly in the Waru Sub-district, Penajam Paser Utara, East Kalimantan, which is one of the main producers. However, production conditions in the region tend to fluctuate due to the limited involvement of existing institutions, challenges that weaken their role and effectiveness, and strategic programs aimed at increasing oil palm production. This study analyzes the relevant institutional structures, identifies constraints that weaken their roles, and determines strategic programs to increase oil palm production. The study used Interpretative Structural Modelling as its analysis method. The results of the analysis show that the Agricultural Extension Centre plays an important role in increasing oil palm production. The main factor contributing to the limited effectiveness of this institution is the lack of skilled human resources. The findings of this study can be used as a practical guide by the government and relevant agencies to strengthen the role of agricultural institutions, particularly the Agricultural Extension Centre, in increasing oil palm production. The implementation of strategies such as improving the human resources of extension workers and empowering farmer groups can increase the effectiveness of programs for developing oil palm in a sustainable manner.